Psychology interventions with adolescents diagnosed with depression (Research, Society and Development, 2023)
Psychology interventions can result in relevant changes in adolescents diagnosed with depression. Therefore, this study has as general objective to identify psychology interventions in adolescents with depression, and the psychosocial factors involved in the disease process in young people, this study also aims to identify which symptoms are most evident in depression that affect this audience. This manuscript is integrative review of scholarly articles published from 2016 to 2021, registered in the PUBMED and LILACS databases and descriptors used in the following languages: English (Psychology and adolescent and depression), Spanish (Psicología y adolescência y depresión), Portuguese (psicologia and and depressão and adolescente). Data was tabulated and analyzed using descriptive statistics. Seventeen articles met inclusion criteria, the majority of which were published in the database PUBMED 12 (70.5%). The most articles were in English (about 13, which corresponds to 76.5%), as well as most articles were produced in the year 2017 (41.2%). The following themes axes were found, as follows: symptoms and risk factors, and interventions and prevention. It is concluded that negative aspects such as hopelessness, loneliness and helplessness can act as risk factors for the development of depressive symptoms in adolescents. On the other hand, positive characteristic, such as self-esteem, self-efficacy, and self-concept, make it possible to face difficulties in a more adaptive way. Studies indicate that people who go through the Psychotherapeutic process have a greater possibility of improvement in depressive symptoms, which is difficult to treat.